Occupational career attainment during modernization. A study of Dutch men in 841 municipalities between 1865 and 1928 - Schulz, Wiebke; Maas, Ineke; van Leeuwen, Marco HD (Acta sociologica, 2015)
This paper addresses the effects of modernization processes on occupational career attainment. We ask whether modernization processes increased the success of occupational careers, and whether the effect of social background varies by regional level of modernization. We analyse a unique data set with information about the careers of around 7000 men who were active in the labour market in the Netherlands between 1865 and 1928. Modernization processes are measured at the municipality level (e.g. presence of post office and train station, educational expansion). The results of cross-classified multilevel growth models show that in municipalities with more advanced modernization, men enjoy higher social status at the beginning of their career, but that their status grows more slowly over the course of their career. The effect of social background hardly varies in response to modernization processes. Our results indicate that regional modernization processes have had restricted impact on individual mobility outcomes.